Coffe without Milk, School without Concept: Traits, Operations and Readings on the Slovenian School (Res Publica. Revista de Historia de las Ideas Políticas, 2020)
The following paper presents a broader picture of Slavoj Žižek’s philosophy, showing that his philosophy is part of a wider group that we call “Slovenian School”. This article has two parts. The first part is devoted to the historical context and the origins of the Slovenian School. The second part sustain two thesis: 1) there is a Slovenian School as impersonal subjet, what implies that reading one of their authors makes another author more comprehensible; and, 2) in spite of the absence of concepts it this School, it is possible to find original traits, operations and readings in common among their members.